Epitaxial growth of CsPbBr3/PbS single-crystal film heterostructures for photodetection. (November 2021) - Wang, Yifan; Li, Xuanze; Liu, Pei; Xia, Jing; Meng, Xiangmin
Abstract: Epitaxial high-crystallization film semiconductor heterostructures has been proved to be an effective method to prepare single-crystal films for different functional devices in modern microelectronics, electro-optics, and optoelectronics. With superior semiconducting properties, halide perovskite materials are rising as building blocks for heterostructures. Here, the conformal vapor phase epitaxy of CsPbBr3 on PbS single-crystal films is realized to form the CsPbBr3 /PbS heterostructures via a two-step vapor deposition process. The structural characterization reveals that PbS substrates and the epilayer CsPbBr3 have clear relationships: CsPbBr3 (110) // PbS(100), CsPbBr3 [ ] // PbS[001] and CsPbBr3 [001] // PbS[010]. The absorption and photoluminescence (PL) characteristics of CsPbBr3 /PbS heterostructures show the broadband light absorption and efficient photogenerated carrier transfer. Photodetectors based on the heterostructures show superior photoresponsivity of 15 A/W, high detectivity of 2.65 × 10 11 Jones, fast response speed of 96 ms and obvious rectification behavior. Our study offers a convenient method for establishing the high-quality CsPbBr3 /PbS single-crystal film heterostructures and providing an effective way for their application in optoelectronic devices.